Agency responses to a system-driven implementation of multiple evidence-based practices in children's mental health services - Jennifer Regan; Anna S. Lau; Miya Barnett; Nicole Stadnick; Alison Hamilton; Keri Pesanti; Lillian Bando; Lauren Brookman-Frazee (BMC, 2017)
Abstract Background Large mental health systems are increasingly using fiscal policies to encourage the implementation of multiple evidence-based practices (EBPs). Although many implementation strategies have been identified, little is known about the types and impacts of strategies that are used by organizations within implementation as usual. This study examined organizational-level responses to a fiscally-driven, rapid, and large scale EBP implementation in children's mental health within the Los Angeles County Department of Mental Health. Methods Qualitative methods using the principles of grounded theory were used to characterize the responses of 83 community-based agencies to the implementation effort using documentation from site visits conducted 2 years post reform. Results Findings indicated that agencies perceived the rapid system-driven implementation to have both positive and negative organizational impacts. Identified challenges were primarily related to system implementation requirements rather than to characteristics of specific EBPs. Agencies employed a variety of implementation strategies in response to the system-driven implementation, with agency size associated with implementation strategies used. Moderate- and large-sized agencies were more likely than small agencies to have employed systematic strategies at multiple levels (i.e., organization, therapist, client) to support implementation. Conclusions These findings are among the first to characterize organizational variability in response to system-driven implementation and suggest ways that implementation interventions might be tailored by organizational characteristics.